PRODUCTION OF READY-TO-EAT EGG WHITE PORRIDGE IN RETORT POUCH - Deeprasert, Aratchaporn; Vatthanakul, Suteera (Srinakharinwirot University Journal of Sciences and Technology, 2023)
Food consumption patterns are now changing and consumer demand is driving for consumption of healthier breakfasts. Porridge is one of the most popular breakfasts for Thai consumers. This research has developed a ready-to-eat egg white porridge in a retort pouch. The effect of temperature and heating time on the physical, microbiological, and sensory properties of egg white porridge in retort pouch was studied under two conditions (1) 121 °C for 18 minutes and (2) 115 °C for 31 minutes, respectively. The result found that the lower temperatures and the longer sterilization time resulted in a decreased L* value of the egg white porridge, while b* value and viscosity increased significantly (p < 0.05). Egg white porridge that was sterilized in both conditions had the F0 values greater than 4 minutes and neither all total microorganisms nor thermophilic bacteria were detected which can be considered safe for consumption. The sensory properties of sterilized egg white porridge were evaluated with 50 consumers by using the 9-point hedonic scale. It was found that egg white porridge was sterilized at 121 °C for 18 minutes received the overall liking score over egg white porridge was sterilized at 115 °C for 31 minutes.